C-Phycocyanin prevents acute myocardial infarction-induced oxidative stress, inflammation and cardiac damage - Vanessa Blas-Valdivia; Daniela Nikita Moran-Dorantes; Placido Rojas-Franco; Margarita Franco-Colin; Neda Mirhosseini; Reza Davarnejad; Ahmad Halajisani; Omid Tavakoli; Edgar Cano-Europa (Taylor & Francis Group, 2022)
Context C-Phycocyanin is a protein with anti-scavenger, antioxidant and anti-inflammatory actions against agents that cause cellular damage. The cardioprotective action of C-phycocyanin against acute myocardial infarction (AMI) has not been studied in animal models.Objective To investigate C-phycocyanin's effect on oxidative stress, inflammation and cardiac damage in a model of isoproterenol-induced AMI.Materials and methods Wistar rats were divided into four groups: (1) sham + vehicle (0.9% saline solution by oral gavage, OG); (2) sham + C-phycocyanin (50 mg/kg/d, OG); (3) AMI + vehicle, and (4) AMI + C-phycocyanin. AMI was induced by administering isoproterenol (20, 10, 5 and 3 mg/kg each dose per day), and serum cardiac enzymes were quantified. After five days, the animals were euthanized; the heart was dissected to determine oxidative stress, redox environment, inflammation and cardiac damage markers.Results We observed that C-phycocyanin reduced AMI-increased cardiac enzymes (CK by about 53%, CKMB by about 60%, AST by about 16% and ALT by about 21%), lipid peroxidation (57%), reactive oxygen species (50%), nitrites (46%), oxidized glutathione (41%), IL1β (3%), INFγ (5%), TNFα 3%), Bcl2 (37%), Bax (43%), COX2 (21%) and caspase 9 (61%). Finally, C-phycocyanin reduced AMI-induced aberrant histological changes related to myonecrosis, interstitial oedema and inflammatory infiltration in the heart muscle.Conclusions C-Phycocyanin prevents AMI-induced oxidative stress, inflammation and heart damage. This study is the first report that employed C-phycocyanin in an animal model of AMI and supports the potential use of C-phycocyanin in the management of AMI.